MODEL PJBL DENGAN LEMBAR KWL DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Astri May Handayani; Uki Suhendar; Senja Putri Merona (STKIP Andi Matappa, 2020)
Creative thinking is a person’s ability that needs to be developed in school and it’s hoped that the teacher can realize learning that makes creative thinking skills can be developed. The combination of the PjBL model with the KWL worksheet is done as needed. This study has the goal of describing the PjBL model combined with the KWL worksheet in improving or enhancing student’s creative thinking skills. The method used for this study examines the literature by collecting written material from articles in journals and books that discuss the PjBL model and KWL. From this study the results obtained from research that produce mathematical creative students who are subjected to the PjBL model with the KWL worksheet with those who are subjected to the PjBL model with the KWL worksheet with those who are subjected to learning models of mathematical creative thinking ability that can be supported by a combination of the PjBL model with the contents of the KWL worksheet. With the stages of the PjBL model combined with this KWL worksheet, students can better understand the material learned through mathematical problem-solving processes by making projects through real work increasing student motivation. The use of the KWL worksheet can organize learning activities more efficiently and systematically and can overcome the problem of using time on the PjBL model so that it’s more focused on learning activities.